PROBLEM-BASED LEARNING MODEL IN IMPROVING LEARNING ACHIEVEMENT OF FLAT BUILDING MATERIAL IN GRADE THREE ELEMENTARY SCHOOL - Badarudin, Badarudin; Daffa Irwanto, Hilmy; Muslim, Arifin (Universitas Muhammadiyah Purwokerto, 2024)
The research carried out against the background of the low achievement of students in learning mathematics flat building material in class III. The purpose of researchers carrying out research is to increase learning achievement by applying the Problem Based Learning (PBL) model to students. The research used is Classroom Action Research (CAR) with 2 cycles and each cycle is applied to 2 meetings, each meeting consisting of planning, action, observation, and reflection of learning. Tools used by researchers to collect data are written test questions, activity and observation sheets for teachers and activity and observation sheets for students, and documentation. The subjects of this study were 12 students at an elementary school located in Kembaran District, Banyumas Regency. The learning outcomes before the research was conducted had an average learning outcome score of 65.83. Research results and shows the first cycle of the results of the value of students got an average of 83.33. There was an increase in cycle II with an achievement of 92.5 on the average learning value of students. This proves that PBL can increase the learning achievement of grade III students and motivation in flat building material.